PENGARUH BUDAYA KERJA TERHADAP KEMAMPUAN DAN KOMITMEN PEGAWAI PADA KANTOR DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN SIDENRENG RAPPANG - Citta, Andi Batary; Ranteta dung, Rilfan Kasi (Jurnal Ilmiah Ecosystem, 2017)
This study aims to analyze the influence of work culture (honesty, perseverance, creativity, discipline, science and technology) on the ability of civil servants in the district disnakertrans sidrap as well as to analyze the influence of work culture on employee commitment in the office of labor and transmigration service district sidenreng rappang. Collecting data is done through direct observation and survey obtained by way of distribution of questionnaires to the respondents.The population in this study is civil servants who actually carry out their duties and responsibilities, as many as 35 people because the number of employees a little then all the population sampled, using descriptive analysis, validity and rentabilktas analysis, multiple regression analysis and hypothesis testing analysis (Test T and Test F). The result of the research is obtained about work culture with work ability, which shows that work culture has a significant influence on the work ability of the employees at the Office of Manpower and Trasmigration of Sidenreng Rappang Regency.Then from result of analysis about work culture to employee's commitment indicate that there is significant influence between work culture with employee commitment at office of Manpower and Trasmigration of Regency of Sidenreng Rappang.